Study of electronic structure and angular dependencies of elastic and discrete electrons scattered from the surface of a deformed alloy Ti-6Al-4V; AIP Conference Proceedings; Vol. 2310, iss. 1 : Physical Mesomechanics. Materials with Multilevel Hierarchical Structure and Intelligent Manufacturing Technology - Shulepov I. A. Ivan Anisimovich; Lomygin A. D. Anton Dmitrievich; Botaeva L. B. Larisa Borisovna; Laptev R. S. Roman Sergeevich; Narkevich N. A. Nataljya Arkadjevna; Kashkarov E. B. Egor Borisovich; Syrtanov M. S. Maksim Sergeevich (2020, 2020)
Title screen